CHARACTERISATION OF SOLID AND LIQUID PINEAPPLE WASTE - Abdullah Abdullah; Hanafi Mat (Dept. of Chemical Engineering, Diponegoro University, 2008)
The pineapple waste is contain high concentration of biodegradable organic material and suspended solid. As a result it has a high BOD and extremes of pH conditions. The pineapple wastes juice contains mainly sucrose, glucose, fructose and other nutrients. The characterisation this waste is needed to reduce it by recycling to get raw material or for conversion into useful product of higher value added products such as organic acid, methane , ethanol, SCP and enzyme. Analysis of sugar indicates that liquid waste contains mainly sucrose, glucose and fructose. The dominant sugar was fructose, glucose and sucrose. The fructose and glucose levels were similar to each other, with fructose usually slightly higher than glucose. The total sugar and citric acid content were 73.76 and 2.18 g/l. The sugar content in solid waste is glucose and fructose was 8.24 and 12.17 %, no sucrose on this waste